Near-infrared fluorescent clip guided gastrectomy: Report of 2 cases (Case reports). (July 2020) - Narihiro, Satoshi; Yoshida, Masashi; Ohdaira, Hironori; Takeuchi, Hideyuki; Kamada, Teppei; Marukuchi, Rui; Suzuki, Norihiko; Hoshimoto, Sojun; Sato, Takayuki; Suzuki, Yutaka
Abstract: Introduction: This is the first report on near-infrared fluorescent (NIRF) clip-guided gastrectomy. The NIRF clip, ZEOCLIP FS, emits NIRF signals when excited. We hypothesized that preoperative placement of the ZEOCLIP FS near a gastric lesion would allow fluorescence laparoscopic localization of the clip, and hence, the lesion, during surgery. We report this technique in two cases. Case presentation: Case 1: An 81-year-old female was diagnosed with early gastric cancer and a pedunculated 4 cm large hyperplastic polyp that had prolapsed into the duodenum, and was scheduled for laparoscopy-assisted distal gastrectomy, due to the potential risk of dissection of the polyp with the duodenal wall. On the day before surgery, ZEOCLIP FS clips were endoscopically placed at the cancer site and the polyp. The locations of the fluorescent clips were confirmed intraoperatively using a full-color fluorescence laparoscope. Case 2: An 81-year-old male was scheduled for laparoscopy-assisted total gastrectomy for gastric cancer under fluorescent clip-guidance. Clip locations could not be confirmed during initial intraoperative observation. However, when the stomach wall was raised using forceps during a second observation attempt, the fluorescent clip locations were confirmed. Discussion: In case 1, it was easy to confirm clip location, facilitating complete resection of early gastric cancer without dissecting the polyp. In case 2, the fluorescent clip was located by raising the stomach and adjusting the angle between the stomach wall and the fluorescence laparoscope. Conclusion: The positive results of these two cases warrant conducting feasibility studies for use of this method. Highlights: This is the first case series on near-infrared fluorescent clip guided gastrectomy. It was possible to observe the position by devising the angle between the stomach wall and the fluorescent laparoscope. The near-infrared clip method may be useful as a method for confirming an intraoperative lesion site in gastrectomy.